2016
DOI: 10.1371/journal.pone.0154863
|View full text |Cite
|
Sign up to set email alerts
|

Computer Aided Diagnosis for Confocal Laser Endomicroscopy in Advanced Colorectal Adenocarcinoma

Abstract: IntroductionConfocal laser endomicroscopy (CLE) is becoming a popular method for optical biopsy of digestive mucosa for both diagnostic and therapeutic procedures. Computer aided diagnosis of CLE images, using image processing and fractal analysis can be used to quantify the histological structures in the CLE generated images. The aim of this study is to develop an automatic diagnosis algorithm of colorectal cancer (CRC), based on fractal analysis and neural network modeling of the CLE-generated colon mucosa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…Two were focused on automated pathological prediction and two exclusively on quantitative image quality control steps that aided the physician's interpretation of confocal endomicroscopic images . The former two studies were conducted by Andre et al ., who reported 89.6% accuracy in the differentiation of adenoma from non‐neoplastic polyps, and Stefanescu et al ., who showed 84.5% accuracy in distinguishing advanced CRC from normal colon mucosa . Both diagnostic algorithms were based on k‐nearest neighbor classification and neural network analysis.…”
Section: Automated Polyp Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two were focused on automated pathological prediction and two exclusively on quantitative image quality control steps that aided the physician's interpretation of confocal endomicroscopic images . The former two studies were conducted by Andre et al ., who reported 89.6% accuracy in the differentiation of adenoma from non‐neoplastic polyps, and Stefanescu et al ., who showed 84.5% accuracy in distinguishing advanced CRC from normal colon mucosa . Both diagnostic algorithms were based on k‐nearest neighbor classification and neural network analysis.…”
Section: Automated Polyp Characterizationmentioning
confidence: 99%
“…51,52 The former two studies were conducted by Andre et al, who reported 89.6% accuracy in the differentiation of adenoma from nonneoplastic polyps, 49 and Stefanescu et al, who showed 84.5% accuracy in distinguishing advanced CRC from normal colon mucosa. 50 Both diagnostic algorithms were based on k-nearest neighbor classification and neural network analysis. Unfortunately, they were evaluated in experimental settings only, with no follow-up clinical trials.…”
Section: Confocal Endomicroscopymentioning
confidence: 99%
“…Compared with CADe in which white-light endoscopy is used as the target of the image analysis, several optical technologies can be used for CADx: white light endoscopy, 25,26 magnifying narrow-band imaging (NBI), [27][28][29][30][31][32] magnifying chromoendoscopy, 33 endocytoscopy, 13,[34][35][36][37] confocal laser endomicroscopy, 38,39 spectroscopy, 40,41 and autofluorescence endoscopy. 42,43,44 Among these, the most extensively studied has been magnifying NBI; 29 probably because it may have better diagnostic performance than nonmagnified NBI and does not require staining like dye-based chromoendoscopy that can be time consuming in routine clinical use.…”
Section: B) Cadxmentioning
confidence: 99%
“…After several pilot studies, 34,35,37,45,46 this research group conducted a large-scale prospective study using CADx, demonstrating 91.4% sensitivity, 91.7% specificity, 88.9% PPV, and 93.7% NPV in the classification of diminutive rectosigmoid adenomas. CADx has also been explored for other modalities such as confocal laser endomicroscopy 38,39 and autofluorescence endoscopy. 42,43 However, the number of publications and performance of the developed models are limited when compared with the aforementioned modalities.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…It is likely that fully automated computer-aided diagnosis will reduce the dependence on optical diagnosis obtained in real time through CLE. In addition, it may reduce the interobserver variability associated with qualitative CLE analysis of images [33,34].…”
Section: Conclusion From the Studymentioning
confidence: 99%